Effectiveness of Acceptance and Commitment Therapy and Integrated Behavioral Couples Therapy on Intimacy and Family Functioning in Divorce-seeking Couples - Seyed Esmaeil Mousavi Haghighi; Ali Pooladi Rishehri1; Seyed Asghar Mousavi (Gonabad University of Medical Sciences, 2022)
Background: Dysfunctional families suffer from poor communication, negative relationships, and countless conflicts. Achieving goals is challenging in such families and requires significant energy. The present study aims to investigate the effectiveness of acceptance and commitment therapy (ACT) and integrated behavioral couples therapy (IBCT) in improving intimacy and family functioning in divorce-seeking couples in Bushehr City, Iran in 2020. Methods: This was a quasi-experimental study based on a pretest-posttest design with a control group. The study population consisted of all married couples applying for a divorce in Bushehr City, Iran. A total of 45 couples were selected as the sample through convenience sampling and were randomly and equally assigned to three groups. The research instruments included, Walker and Thompson intimacy scale, and the McMaster family assessment device. The data were statistically analyzed by univariate and multivariate analysis of covariance via SPSS software. The Bonferroni post hoc test was used to determine the mean difference between the groups. Results: The results showed a significant difference between ACT and IBCT groups with the control group in the posttest scores for intimacy and family functioning (P<0.001). Moreover, there was no significant difference between ACT and IBCT in improving intimacy and family functioning in divorce-seeking couples. Conclusion: Based on the results of the present study, both ACT and IBCT can be used for improving intimacy and family functioning between divorce-seeking couples.